2023
DOI: 10.1111/phor.12445
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of conventional and deep learning‐based image‐matching methods on diverse datasets

Abstract: Image matching plays an important role in photogrammetry, computer vision and remote sensing. Modern deep learning‐based methods have been proposed for image matching; however, whether they will surpass and take the place of the conventional handcrafted methods in the remote sensing field still remains unclear. A comprehensive evaluation on stereo remote sensing images is also lacking. This paper comprehensively evaluates the performance of conventional and deep learning‐based image‐matching methods by dividin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The unevenly distributed tie points require manual adjustments. Although learning-based image matching methods have shown promising performance, recent studies have demonstrated that these methods do not have obvious advantages over handcrafted ones in conventional 3D reconstruction tasks [39][40][41][42]. Directly applying these learning-based methods to match cross-platform images and reconstruct 3D models of complex urban scenes remains challenging.…”
Section: Related Workmentioning
confidence: 99%
“…The unevenly distributed tie points require manual adjustments. Although learning-based image matching methods have shown promising performance, recent studies have demonstrated that these methods do not have obvious advantages over handcrafted ones in conventional 3D reconstruction tasks [39][40][41][42]. Directly applying these learning-based methods to match cross-platform images and reconstruct 3D models of complex urban scenes remains challenging.…”
Section: Related Workmentioning
confidence: 99%
“…The stereo positioning of remote sensing images involves calculating ground point coordinates using a space intersection method based on a geometric positioning model of remote sensing images and the homologous points of stereo image pairs (Albanwan & Qin, 2022; Deng et al., 2019; Ji et al., 2023; Luo, Qiu, Peng, et al., 2022). Remote sensing satellites typically include optical, synthetic aperture radar (SAR) and laser altimetry satellites.…”
Section: Introductionmentioning
confidence: 99%
“…The active type includes techniques like lidar, structured light and RGBD cameras. The passive type also referred to as image‐based 3D reconstruction (Ji et al., 2023; Remondino & El‐Hakim, 2006), involves a sequential workflow of image retrieval, feature extraction and matching, sparse reconstruction and dense reconstruction using photographs captured from multiple viewpoints (Griwodz et al., 2021). The primary goal of this process is to recover the 3D model of the scene by matching corresponding points and determining the geometric relationships between multiple views.…”
Section: Introductionmentioning
confidence: 99%